Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1182/blood.v96.9.3231
|View full text |Cite
|
Sign up to set email alerts
|

Nonopsonic monocyte/macrophage phagocytosis of Plasmodium falciparum–parasitized erythrocytes: a role for CD36 in malarial clearance

Abstract: Plasmodium falciparum is the most lethal form of malaria and is increasing both in incidence and in its resistance to antimalarial agents. An improved understanding of the mechanisms of malarial clearance may facilitate the development of new therapeutic interventions. We postulated that the scavenger receptor CD36, an important factor in cytoadherence of P falciparum–parasitized erythrocytes (PEs), might also play a role in monocyte- and macrophage-mediated malarial clearance. Exposure of nonopsonized PEs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(120 citation statements)
references
References 78 publications
6
112
1
1
Order By: Relevance
“…This is in agreement with the finding that synthesis of procoagulant tissue factor by endothelial cells is induced by serum from malaria patients in a TNF-alpha dependent manner (Hemmer et al 1991a;Bierhaus et al 1995), but not by P. falciparum parasitized erythrocytes, which bind to the vascular endothelium (mature stages; authors' data, not shown). Similarly, binding and phagocytosis of P. falciparum-parasitized erythrocytes by monocytes fails to stimulate TNF-alpha production (McGilvray et al 2000). These findings indicate that endothelial sequestration of parasitized erythrocytes is unlikely to augment the host response in P. falciparum malaria.…”
Section: Discussionmentioning
confidence: 86%
“…This is in agreement with the finding that synthesis of procoagulant tissue factor by endothelial cells is induced by serum from malaria patients in a TNF-alpha dependent manner (Hemmer et al 1991a;Bierhaus et al 1995), but not by P. falciparum parasitized erythrocytes, which bind to the vascular endothelium (mature stages; authors' data, not shown). Similarly, binding and phagocytosis of P. falciparum-parasitized erythrocytes by monocytes fails to stimulate TNF-alpha production (McGilvray et al 2000). These findings indicate that endothelial sequestration of parasitized erythrocytes is unlikely to augment the host response in P. falciparum malaria.…”
Section: Discussionmentioning
confidence: 86%
“…Recent data suggest that this unknown surface ligand might interact directly or indirectly with the parasite-derived schizont membrane-associated cytoadherence protein that is exported to the cytoplasm of infected erythrocytes [13]. CD36 is also expressed on the surface of macrophages and monocytes, where it serves as a receptor that mediates the recognition and phagocytosis of infected erythrocytes [39][40][41]. Most of the reports that used Cd36 2/2 animals to study malaria in the lungs observed a significant reduction in the lung parasite burden and ALI [15,16] but could not differentiate the contributions of the endothelial cell-expressed and monocyte/macrophage-expressed CD36 to the phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The scavenger receptor CD36 is expressed on lung vascular endothelial cells, where it mediates the sequestration of malariainfected erythrocytes [13,37,38], and on the surface of mononuclear cells, where it serves as a receptor for nonopsonic phagocytosis of Plasmodium-infected erythrocytes [39][40][41]. Although the importance of CD36 in the sequestration of parasitized erythrocytes to endothelial surfaces in the lungs has been demonstrated [16], the role of CD36 on myeloid cell populations in controlling malaria-associated respiratory distress is less clearly defined.…”
Section: Cd36 and Malaria-induced Alimentioning
confidence: 99%
“…This process requires the pathogen to be phagocytosed and degraded in phagolysosomes of professional antigen‐presenting cells, such as DC and macrophages (9). During blood stage malaria infection, Plasmodium multiplies within RBCs and these infected RBCs (iRBC) are efficiently phagocytosed by DC and macrophages (10,11). The phagocytosis of Plasmodium ‐iRBC has been studied both in vitro and in vivo (11,12); however, the processing of Plasmodium‐ iRBC by DC and macrophages has not been characterized in detail.…”
Section: Introductionmentioning
confidence: 99%